2020
DOI: 10.1038/s41416-020-1007-3
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of G6PD induces the expression and bisecting GlcNAc-branched N-glycosylation of E-Cadherin to block epithelial-mesenchymal transition and lymphatic metastasis

Abstract: Background As the rate-limit enzyme of the pentose phosphate pathway, glucose-6-phosphate dehydrogenase (G6PD) plays important roles in tumour progression, but the exact mechanism through which G6PD controls cancer metastasis remains unclear. Methods G6PD expression in resected oral squamous cell carcinoma (OSCC) samples was analysed by immunohistochemistry. The effects and mechanism of G6PD suppression on OSCC cell lines were measured by transwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…It has been demonstrated that G6PD regulates many signaling pathways [65][66][67]. The study of Wang et al suggests that the inhibition of G6PD is associated with invasion, metastasis and EMT of oral squamous cell carcinoma (OSCC) through activating JNK, which enhances the E-Cadherin expression level and regulates MGAT3 expression transcriptionally to promote the bisecting GlcNAc-branched N-glycosylation of E-Cadherin [65] (Figure 6a).…”
Section: Other Pathways Related To G6pd In Cancermentioning
confidence: 98%
“…It has been demonstrated that G6PD regulates many signaling pathways [65][66][67]. The study of Wang et al suggests that the inhibition of G6PD is associated with invasion, metastasis and EMT of oral squamous cell carcinoma (OSCC) through activating JNK, which enhances the E-Cadherin expression level and regulates MGAT3 expression transcriptionally to promote the bisecting GlcNAc-branched N-glycosylation of E-Cadherin [65] (Figure 6a).…”
Section: Other Pathways Related To G6pd In Cancermentioning
confidence: 98%
“…However, G6PD silencing did moderately decrease lung colonisation when breast cancer cells were delivered through tail-vain injection [ 49 ]. A similar decrease of metastatic activity and no change of the primary tumour growth were observed when PPP activity was inhibited in melanoma [ 50 ], tongue cancer [ 51 ] or other oral squamous cell carcinomas [ 52 ].…”
Section: Citrate In Redox Balancementioning
confidence: 70%
“…However, G6PD silencing did moderately decrease lung colonisation when breast cancer cells were delivered through tail-vain injection [49]. A similar decrease of metastatic activity and no change of the primary tumour growth were observed when PPP activity was inhibited in melanoma [50], tongue cancer [51] or other oral squamous cell carcinomas [52]. K-Ras-driven tumours are known to rely heavily on glycolysis with increased glucose uptake, decreased Krebs cycle activity, increased glutamine use and reduced oxidative PPP [53,54].…”
Section: Pentose Phosphate Pathwaymentioning
confidence: 77%
“…Glycosylation, a key regulatory mechanism, is involved in kinds of cancer-related processes. 26,27 Abnormal glycosylation is a common phenomenon that has been observed in cancer, and it can determine cancer stage, grade, and the fate of cancer progression. [28][29][30] It is a contributor to the occurrence and development of cancers, including bladder cancer.…”
Section: Discussionmentioning
confidence: 99%